Temperature‐associated habitat selection in a cold‐water marine fish. (23rd November 2015) - Freitas, Carla; Olsen, Esben M.; Knutsen, Halvor; Albretsen, Jon; Moland, Even
Summary: Habitat selection is a complex process, which involves behavioural decisions guided by the multiple needs and constraints faced by individuals. Climate‐induced changes in environmental conditions may alter those trade‐offs and resulting habitat use patterns. In this study, we investigated the effect of sea temperature on habitat selection and habitat use of acoustically tagged Atlantic cod ( Gadus morhua ) at the Norwegian Skagerrak coast. Significant relationships between ocean temperature and habitat selection and use were found. Under favourable sea temperature thresholds (<16 °C), cod selected vegetated habitats, such as eelgrass and macroalgae beds, available in shallow areas. Selection for those habitats was especially high at night, when cod tended to ascend to shallower areas, presumably to feed. Selection and use of those habitats decreased significantly as temperature rose. Under increased sea surface temperature conditions, cod were absent from vegetated shallow habitats, both during the day and night, and selected instead non‐vegetated rocky bottoms and sand habitats, available in deeper, colder areas. This study shows the dynamic nature of habitat selection and strongly suggests that cod in this region have to trade off food availability against favourable temperature conditions. Future increases in ocean temperature are expected to further influence the spatial behaviour of marine fish, potentially affecting individual fitness and population dynamics. Abstract : This study found that habitat selection of acoustically tagged cod in Skagerrak was highly dynamic and associated with changes in ocean temperature. The study strongly suggests that cod in this region have to trade off food availability against favourable temperature conditions. Future increases in ocean temperature are expected to further influence the spatial behaviour of marine fish, potentially affecting individual fitness and population dynamics. Photo Credit: Øystein Paulsen.